Grain boundary amorphization as a strategy to mitigate lithium dendrite growth in solid-state batteries - Yiwei You; Dexin Zhang; Zhifeng Wu; Tie-Yu Lü; Xinrui Cao; Yang Sun; Zi-Zhong Zhu; Shunqing Wu (Nature Communications)
Abstract Solid-state lithium metal batteries using garnet-type Li7La3Zr2O12 electrolytes hold immense promise for next-generation energy storage, but grain boundary defects promote lithium redistribution and dendrite formation, compromising performance and safety. To address this, we investigate lithium behavior at these boundaries using machine learning potentials and molecular dynamics simulations. Energy minimization drives lithium accumulation or depletion at grain boundaries depending on cavity fraction and local lithium concentration. Crack-like boundary voids facilitate lithium protrusions and dendrites at the electrolyte/negative electrode interface, increasing short-circuit risks. Controlled grain boundary melting achieves selective amorphization while preserving bulk crystallinity. This structural modification slightly reduces ionic conductivity but enhances interfacial electronic and mechanical properties, suppressing lithium aggregation and alleviating interfacial protrusions. In this work, we demonstrate how grain boundary structures govern lithium redistribution dynamics and dendrite formation mechanisms. We further propose targeted grain boundary amorphization as an effective strategy to engineer robust solid-state electrolyte microstructures that improve battery cyclability and safety.